Cortical [18F]PI‐2620 Binding Differentiates Corticobasal Syndrome Subtypes. Issue 9 (5th May 2021) - Palleis, Carla; Brendel, Matthias; Finze, Anika; Weidinger, Endy; Bötzel, Kai; Danek, Adrian; Beyer, Leonie; Nitschmann, Alexander; Kern, Maike; Biechele, Gloria; Rauchmann, Boris‐Stephan; Häckert, Jan; et al.
Abstract: Background: Corticobasal syndrome is associated with cerebral protein aggregates composed of 4‐repeat (~50% of cases) or mixed 3‐repeat/4‐repeat tau isoforms (~25% of cases) or nontauopathies (~25% of cases). Objectives: The aim of this single‐center study was to investigate the diagnostic value of the tau PET‐ligand [ 18 F]PI‐2620 in patients with corticobasal syndrome. Methods: Forty‐five patients (71.5 ± 7.6 years) with corticobasal syndrome and 14 age‐matched healthy controls underwent [ 18 F]PI‐2620‐PET. Beta‐amyloid status was determined by cerebral β‐amyloid PET and/or CSF analysis. Subcortical and cortical [ 18 F]PI‐2620 binding was quantitatively and visually compared between β‐amyloid‐positive and ‐negative patients and controls. Regional [ 18 F]PI‐2620 binding was correlated with clinical and demographic data. Results: Twenty‐four percent (11 of 45) were β‐amyloid‐positive. Significantly elevated [ 18 F]PI‐2620 distribution volume ratios were observed in both β‐amyloid‐positive and β‐amyloid‐negative patients versus controls in the dorsolateral prefrontal cortex and basal ganglia. Cortical [ 18 F]PI‐2620 PET positivity was distinctly higher in β‐amyloid‐positive compared with β‐amyloid‐negative patients with pronounced involvement of the dorsolateral prefrontal cortex. Semiquantitative analysis of [ 18 F]PI‐2620 PET revealed a sensitivity of 91% for β‐amyloid‐positive and of 65% for β‐amyloid‐negative cases, which is in excellent agreement with prior clinicopathological data. Regardless of β‐amyloid status, hemispheric lateralization of [ 18 F]PI‐2620 signal reflected contralateral predominance of clinical disease severity. Conclusions: Our data indicate a value of [ 18 F]PI‐2620 for evaluating corticobasal syndrome, providing quantitatively and regionally distinct signals in β‐amyloid‐positive as well as β‐amyloid‐negative corticobasal syndrome. In corticobasal syndrome, [ 18 F]PI‐2620 may potentially serve for a differential diagnosis and for monitoring disease progression. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society